Sensory Gating Capacity and Attentional Function in Adults With ADHD: A Preliminary Neurophysiological and Neuropsychological Study. Issue 10 (August 2019) - Micoulaud-Franchi, Jean-Arthur; Lopez, Régis; Cermolacce, Michel; Vaillant, Florence; Péri, Pauline; Boyer, Laurent; Richieri, Raphaëlle; Bioulac, Stéphanie; Sagaspe, Patricia; Philip, Pierre; Vion-Dury, Jean; Lancon, Christophe
Objective: The inability to filter sensory input correctly may impair higher cognitive function in ADHD. However, this relationship remains largely elusive. The objectives of the present study is to investigate the relationship between sensory input processing and cognitive function in adult patients with ADHD.Method: This study investigated the relationship between deficit in sensory gating capacity (P50 amplitude changes in a double-click conditioning-testing paradigm and perceptual abnormalities related to sensory gating deficit with the Sensory Gating Inventory [SGI]) and attentional and executive function (P300 amplitude in an oddball paradigm and attentional and executive performances with a neuropsychological test) in 24 adult patients with ADHD.Results: The lower the sensory gating capacity of the brain and the higher the distractibility related to sensory gating inability that the patients reported, the lower the P300 amplitude.Conclusion: The capacity of the brain to gate the response to irrelevant incoming sensory input may be a fundamental protective mechanism that prevents the flooding of higher brain structures with irrelevant information in adult patients with ADHD.